ANALISIS PERAN QUALITY MANAGEMENT PRACTICES DAN INTERNAL KNOWLEDGE TRANSFER TERHADAP KINERJA ORGANISASIONAL PADA PERGURUAN TINGGI NEGERI DI KOTA PADANG - Firman Firman (Jurnal Praktik Bisnis, 2016)
This study aims to identify and analyze the influence of quality management practices and internal knowledge transfer to organizational performance in university in Padang. This is a causative research. The population in this study were all departments in university in Padang. The sample in this research is the department of the state university in Padang. The results showed that the quality management practices significantly influence organizational performance. Keyword: Organizational Performance, Quality Management Practices, Internal Knowledge Transfer.